2020
DOI: 10.1002/pip.3304
|View full text |Cite
|
Sign up to set email alerts
|

Role of silicon surface, polished 〈100〉 and 〈111〉 or textured, on the efficiency of double‐sided TOPCon solar cells

Abstract: We investigate the role of the silicon surface and orientation on double‐sided TOPCon solar cells properties. The solar cells of front and rear, (p) and (n), poly‐Si/SiOx stack, fabricated on polished surfaces oriented 〈100〉 and 〈111〉 and pyramid textured surfaces, are characterized as a function of the thickness of an ultrathin SiOx layer, controlled at atomic scale from one‐ to four‐cycle atomic layer deposition (ALD). Our findings underline that the optimized thickness of the ultrathin SiOx is about 1.1 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…It has been observed that in textured surfaces, the thickness of the oxide and polysilicon can vary, leading to thinner layer stacks at the tips and flanks of the pyramids, as compared with the valleys and flat surfaces. [ 30,31 ] Based on this observation, we suggest that, due to the thinner passivating stack, the tips and flanks of the pyramids are more susceptible to damage caused by the metal paste constituents and hence lead to an overall higher metal polysilicon recombination current density.…”
Section: Resultsmentioning
confidence: 94%
“…It has been observed that in textured surfaces, the thickness of the oxide and polysilicon can vary, leading to thinner layer stacks at the tips and flanks of the pyramids, as compared with the valleys and flat surfaces. [ 30,31 ] Based on this observation, we suggest that, due to the thinner passivating stack, the tips and flanks of the pyramids are more susceptible to damage caused by the metal paste constituents and hence lead to an overall higher metal polysilicon recombination current density.…”
Section: Resultsmentioning
confidence: 94%
“…This is surprising as usually V oc values beyond 700 mV can be obtained for textured surfaces when using the same oxidation process as for planar surfaces. The difference in passivation on planar and textured surfaces is mainly associated with the varying thickness of the thermally grown SiO x due to the different surface orientations and by the reduced passivation quality of the SiO x interlayer on <111> planes 84–86 . Hence, it could be that during the oxidation process some problems occurred, leading to a thinner SiO x on <111> planes or that other processes like texturing or cleaning were not optimal.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, M. Lozac'h's group fabricated the tunnel oxide using a lab-scale remote-plasma plasma-enhanced ALD (PEALD). However, their reported cell V oc < 640 mV and cell efficiency < 19% were not remarkable by current standards [34,35]. Therefore, ALD was not considered a potential method for tunnel oxide fabrication in TOPCon solar cells as, for example, evidenced by review articles by D. Yan [22] and S. W. Glunz [36] published in 2021.…”
Section: Introductionmentioning
confidence: 99%